PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS DAN OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019) - Amani Ruhil; Nurmayanti Poppy; Hariyani Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine and to analyze the effect of liquidity, leverage, profitability and operating capacity to financial distress on consumer goods companies registered in Indonesia Stock Exchange period 2017-2019. This research is a quantitative research. The population of this research is comprised by 46 companies and the amount of companies that qualified the criteria is 16 companies. The sampling method that used in this research is purposive sampling. Analysis method that used is multiple regression analysis with using statistical software SPSS 25. The results showed that liquidity, leverage, profitability and operating capacity had significant effect on financial distress. This shows that if the company has good liquidity, leverage, profitability and operating capacity, it will reduce the occurrence of financial distress company. As a result, the company can run the company's operations well.Keywords: Liquidity, Leverage, Profitability, Operating capacity, Financial distress